Bioactivities of the Green Synthesized Silver Nanoparticles Reduced Using Allium cepa L Aqueous Extracts Induced Apoptosis in Colorectal Cancer Cell Lines. (4th February 2022) - Abdellatif, Ahmed A. H.; Mahmood, Amer; Alsharidah, Mansour; Mohammed, Hamdoon A.; Alenize, Salman Khalaf; Bouazzaoui, Abdellatif; Al Rugaie, Osamah; Alnuqaydan, Abdullah M.; Ahmad, Rehan; Vaali-Mohammad, Mansoor-Ali; Alfayez, Musaad; Traiki, Thamer Bin; et al.
Abstract : Allium cepa L ( A. cepa ) extract is frequently used as an adjuvant food in cancer treatment. We hypothesized that it contains a source of anticancer activity. There is a need to synthesize the silver nanoparticles (AgNPs) using an environment-friendly green synthesis reduction method using an aqueous extract of A. cepa . The AgNPs-CEPA were prepared by reduction method using the aqueous extract of A. cepa . The formed AgNPs-CEPA were characterized for their sizes and charge distribution. The AgNP-CEPA was investigated for its antioxidant and anticancer properties. Cell viability was evaluated by MTT assay. Gene expression was evaluated by real-time polymerase chain reaction (RT-PCR), and apoptosis measurement was carried out by flow cytometry in AgNP-CEPA-treated cells. The results showed a uniform size for AgNPs-CEPA of 155 ± 2.1  nm with a zeta potential of − 37.3 ± − 2.92 mv. The produced AgNPs-CEPA are biocompatible with anticancer action and a moderate level of antioxidant reactivity. AgNPs-CEPA showed better reducing activity for A. cepa extract compared to the AgNPs-CEPA. AgNP-CEPA treatment of human colorectal cancer cell lines (HT-29 and SW620) inhibited cell proliferation and altered Bcl2 family gene expression. Moreover, exposure of cell lines to AgNPs-CEPA resulted in the significant induction of apoptosis compared to A. cepa and AgNO3 . These findings indicate that AgNP-CEPA induces apoptosis by inhibiting Bcl2 family gene expression, suggesting that this formula is a promising anticancer agent for treating colorectal cancer.